1997
DOI: 10.1897/1551-5028(1997)016<2438:eocoia>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorpyrifos on Individuals and Populations of Daphnia Pulex in the Laboratory and Field

Abstract: Abstract-Effects of the insecticide chlorpyrifos (cpf) on young (Ͻ1 d old) and adult (7-9 d old) Daphnia pulex and the ability of D. pulex to recover after exposure were tested in the laboratory. Populations of D. pulex exposed to cpf were studied in the laboratory and field. In the field, cpf was applied in a single dose. The effects of that dose on D. pulex populations were tested and compared with the effects of a simulated single dose and its ensuing decay on populations in the laboratory. The lowest no-ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 12 publications
6
38
0
Order By: Relevance
“…Environmental risk assessment of pesticides for aquatic ecosystems is mostly based on the effects of individual compounds using single-species toxicity tests conducted either under controlled laboratory conditions or in the field [74][75][76]. While the value of these tests is incontestable in establishing safety standards for species protection, their wider ecological relevance has been questioned in recent years.…”
Section: Biomarker Responses To Pesticide Mixturesmentioning
confidence: 99%
“…Environmental risk assessment of pesticides for aquatic ecosystems is mostly based on the effects of individual compounds using single-species toxicity tests conducted either under controlled laboratory conditions or in the field [74][75][76]. While the value of these tests is incontestable in establishing safety standards for species protection, their wider ecological relevance has been questioned in recent years.…”
Section: Biomarker Responses To Pesticide Mixturesmentioning
confidence: 99%
“…Induced individual tolerance from previous pulses may strengthen survivors (making them more tolerant [6]) through acclimation, induction of detoxification or biotransformation enzymes, and so on (e.g., induction of cytochrome P450—dependent mono‐oxygenases [7] and mixed‐function oxygenases in fish [8,9]). Cumulative individual effects occur when the first pulse weakens the organism (making it less tolerant), dissipating energy and lowering organism fitness [6], or the substance irreversibly interacts with the receptor [10,11]. Postexposure, latent, or delayed effects occur after a typical study is terminated.…”
Section: Potential Consequences Of a Time‐varying Or Pulsed Exposurementioning
confidence: 99%
“…Van der Hoeven and Gerritsen [10] studied the effect of chlorpyrifos on Daphnia pulex , reporting that the agrochemical immobilized daphnids several days before death. Even when exposure was discontinued, immobilized D. pulex died, further supporting the concept of irreversible effects.…”
Section: Potential Consequences Of a Time‐varying Or Pulsed Exposurementioning
confidence: 99%
“…In general, a relationship between measured concentrations, results of toxicity tests, and receiving water effects has not been established with organophosphorous pesticides. However, in a recent study with chlorpyrifos and Daphnia pulex , the authors concluded that concentrations associated with effects in the laboratory were very similar to those that produced effects under field conditions [23]. Establishing such a relationship is unlikely to be possible in urban streams that are subject to a variety of contaminants and habitat alterations.…”
Section: Discussionmentioning
confidence: 99%